The Oxford handbook of the prophets - Sharp, Carolyn J. (Oxford handbooks online Religion, 2016)
This volume explores historical, literary, and ideological dimensions of the books of the Latter Prophets of the Hebrew Bible - Isaiah, Jeremiah, Ezekiel, and the Book of the Twelve - along with Daniel. The prophetic books comprise oracles, narratives, and vision reports from ancient Israel and Judah spanning several centuries. Analysis of these texts sheds light on the cultural norms, theological convictions, and political disputes of Israelite and Judean communities in the shadow of the empires of ancient Egypt, Babylonia, and Persia.